2020
DOI: 10.1007/s12550-020-00411-x
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of T-2 toxin and HT-2 toxin during experimental feeding of yellow mealworm (Tenebrio molitor)

Abstract: Within the European Union (EU), edible insects need to be approved as “Novel Food” according to Regulation (EU) 2015/2283 and must comply with the requirements of European food law with regard to microbiological and chemical food safety. Substrates used for feeding insects are susceptible to the growth of Fusarium spp. and consequently to contamination with trichothecene mycotoxins. Therefore, the current study aimed to investigate the influence of T-2 and HT-2 toxins on the larval life cycle of yellow mealwor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 40 publications
(54 reference statements)
0
15
1
Order By: Relevance
“…The study of Piacenza et al ( 2020 ) showed that no T-2, HT-2, T-2 triol, or T-2 tetraol were detected (in levels above the LOD) in the surviving larvae or in the dead larvae collected from the control diets. However, after examination of the dead larvae collected from the other diets, 44.2 μg/kg T-2 was found in the body of the larvae fed with the naturally contaminated diet (250 μg/kg total T-2 and HT-2) and 7.7 μg/kg T-2 in the larvae fed the naturally contaminated diet (100 μg/kg total T-2 and HT-2) and the artificially contaminated diets.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The study of Piacenza et al ( 2020 ) showed that no T-2, HT-2, T-2 triol, or T-2 tetraol were detected (in levels above the LOD) in the surviving larvae or in the dead larvae collected from the control diets. However, after examination of the dead larvae collected from the other diets, 44.2 μg/kg T-2 was found in the body of the larvae fed with the naturally contaminated diet (250 μg/kg total T-2 and HT-2) and 7.7 μg/kg T-2 in the larvae fed the naturally contaminated diet (100 μg/kg total T-2 and HT-2) and the artificially contaminated diets.…”
Section: Resultsmentioning
confidence: 98%
“…250 μg/kg T-2/HT-2 toxins gained 44% more weight than the control group fed a natural diet. Additionally, larval weight gain was significantly higher when fed with an artificially contaminated diet than when fed with naturally contaminated diets (Piacenza et al 2020 ). In general, most studies focused on the effect of mycotoxin exposure on weight gain in T. molitor larvae.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, insects have a fundamental role as pollinators. Wild and managed pollinators are closely linked to human well-being through their pivotal role in wild plant reproduction and crop production, affecting the yield of approximately 75% of the world’s most important crop types [ 3 ]; therefore, we can state that insect pollinators are responsible for one of every three bites of food we eat [ 4 ]. In addition, insects, considered as a food (re)source, appear more sustainable when compared with other sources of animal protein, thus possibly contributing to alleviating the pressure on the environment and the planet in feeding a densely populated world [ 5 ].…”
Section: Introductionmentioning
confidence: 99%